2021
DOI: 10.3390/cancers13174289
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Pembrolizumab with Electrochemotherapy in Cutaneous Metastases from Melanoma: A Comparative Retrospective Study from the InspECT and Slovenian Cancer Registry

Abstract: Electrochemotherapy (ECT) is an effective locoregional therapy for cutaneous melanoma metastases and has been safely combined with immune checkpoint inhibitors in preliminary experiences. Since ECT is known to induce immunogenic cell death, its combination with immune checkpoint inhibitors might be beneficial. In this study, we aimed to investigate the effectiveness of ECT on cutaneous melanoma metastases in combination with pembrolizumab. We undertook a retrospective matched cohort analysis of stage IIIC–IV m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 47 publications
(67 reference statements)
2
29
0
5
Order By: Relevance
“…A retrospective study by Heppt et al [ 125 ] of 33 patients with metastatic melanoma showed 15 months median OS among the five patients that received ECT + anti-PD-1, while the median OS in the ECT + ipilimumab group was not reached. The local and systemic objective response rates were comparable to those in the study by Campana et al [ 124 ].…”
Section: The Synergy Of Electroporation and Immunotherapysupporting
confidence: 84%
See 1 more Smart Citation
“…A retrospective study by Heppt et al [ 125 ] of 33 patients with metastatic melanoma showed 15 months median OS among the five patients that received ECT + anti-PD-1, while the median OS in the ECT + ipilimumab group was not reached. The local and systemic objective response rates were comparable to those in the study by Campana et al [ 124 ].…”
Section: The Synergy Of Electroporation and Immunotherapysupporting
confidence: 84%
“…It found significantly increased OS among the patients that received both local therapy (ECT, radiotherapy, or stereotactic radiation) + ipilimumab (anti-CTLA-4) compared to ipilimumab alone (median OS of 93 weeks vs. 42 weeks), though it should be noted that only 4 in 45 patients received ECT treatment. Recently, the largest retrospective study to date included 130 patients with metastatic melanoma [ 124 ]. Data from the European InspECT group was combined with Slovenian registry data.…”
Section: The Synergy Of Electroporation and Immunotherapymentioning
confidence: 99%
“…The patients treated with pembrolizumab and ECT experienced lower disease progression rates and longer survival than those who received pembrolizumab alone. 32 Similar approach could be by immunostimulation using phIL12 intratumoral GET. Further, different studies combining tumor irradiation and immune checkpoint inhibitors demonstrated the same.…”
Section: Discussionmentioning
confidence: 99%
“…However, only four out of 45 enrolled patients were treated with ECT. Finally, Campana et al, in their recent retrospective analysis, showed how Pembrolizumab combined to ECT in melanoma patients (stage IIIC-IV) improves 1-year PFS and OS (p = 0.034 and p = 0.006, respectively) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%